2018
DOI: 10.1208/s12249-018-1095-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronotherapeutic Drug Delivery of Ketoprofen and Ibuprofen for Improved Treatment of Early Morning Stiffness in Arthritis Using Hot-Melt Extrusion Technology

Abstract: This work developed a chronotherapeutic drug delivery system (CTDDS) utilizing a potential continuous hot-melt extrusion (HME) technique. Ketoprofen (KTP) and ibuprofen (IBU) were used as two separate model drugs. Eudragit S100 (ES100) was the matrix-forming agent, and ethyl cellulose (EC) (2.5 and 5%) was the release-retarding agent. A 16-mm extruder was used to develop the CTDDS to pilot scale. The obtained extrudate strands were transparent, indicating that the drugs were homogeneously dispersed in the matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Over the last three decades, its use in drug delivery and research has tremendously increased owing to the advantages associated with this technology, such as high efficiency, solvent-free, innovative applications, and continuous manufacturing [17]. Although HME is most widely used in the preparation of amorphous solid dispersions, it is also used in the development of many innovative applications, such as taste masking, abuse-deterrent formulations, chronotherapeutic systems, topical formulations, semi-solid dosage forms, and co-amorphous systems [18][19][20][21][22]. Recently, the interest of researchers has shifted to additive manufacturing of pharmaceutical dosage forms where HME is combined with three-dimensional (3D) printing.…”
Section: Of 13mentioning
confidence: 99%
“…Over the last three decades, its use in drug delivery and research has tremendously increased owing to the advantages associated with this technology, such as high efficiency, solvent-free, innovative applications, and continuous manufacturing [17]. Although HME is most widely used in the preparation of amorphous solid dispersions, it is also used in the development of many innovative applications, such as taste masking, abuse-deterrent formulations, chronotherapeutic systems, topical formulations, semi-solid dosage forms, and co-amorphous systems [18][19][20][21][22]. Recently, the interest of researchers has shifted to additive manufacturing of pharmaceutical dosage forms where HME is combined with three-dimensional (3D) printing.…”
Section: Of 13mentioning
confidence: 99%
“…Similar results were found in the literature, where it was not possible to process samples with concentrations higher than 30% of KTO due to their elastic appearance after the cooling process. [21,38,39] Due to the elastic behavior of the samples at room temperature, it was necessary to store the samples in a space with controlled temperature, below 10 C. It was observed that the samples not stored in a space with controlled temperature, their milling was difficult, the powder showed tendency to agglomerate and the hard capsules were left with air inside, which caused them to float affecting negatively the KTO release profile. All samples analyzed were stored in a refrigerator.…”
Section: Hme Hot Melt Extrusionmentioning
confidence: 99%
“…There is information in the literature about processing binary samples (API and one polymer excipient) by HME. [11,12,14,[17][18][19]21,40] The present investigation was done with ternary samples, an API and two polymeric excipients. Although, there is not much information about the interaction of polymeric excipients with each other or with the API.…”
Section: 62mentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, HME is being explored for various applications, and it is found successful in the development of various drug delivery strategies. Literature reports showed the use of HME in the development of pharmaceutical cocrystals [8], co-extrusion for producing fixed-dose combinations [9], chronotherapeutic systems [10], self-emulsifying drug delivery systems [11], twin-screw granulation [12], semisolid dosage forms [13], abuse-deterrent formulations [14], novel three-dimensional (3D) printing filaments [15], and other miscellaneous applications [2,3,4,16]. Figure 1 illustrates the volume of research publications on HME for preparing different drug delivery sytems during the last five years.…”
Section: Introductionmentioning
confidence: 99%